2008
DOI: 10.1105/tpc.107.055137
|View full text |Cite
|
Sign up to set email alerts
|

The AGL62 MADS Domain Protein Regulates Cellularization during Endosperm Development inArabidopsis 

Abstract: Endosperm, a storage tissue in the angiosperm seed, provides nutrients to the embryo during seed development and/or to the developing seedling during germination. A major event in endosperm development is the transition between the syncytial phase, during which the endosperm nuclei undergo many rounds of mitosis without cytokinesis, and the cellularized phase, during which cell walls form around the endosperm nuclei. The molecular processes controlling this phase transition are not understood. In agl62 seeds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
268
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(285 citation statements)
references
References 77 publications
16
268
1
Order By: Relevance
“…S17), implicating a differential transcriptional regulation between embryo and endosperm. It was previously reported that TFs of MADS function in seed and endosperm development (Kang et al, 2008;Sreenivasulu et al, 2008;Bemer et al, 2010;Le et al, 2010;Agarwal et al, 2011;Hehenberger et al, 2012). AGL62, a MADS protein of Arabidopsis, is the direct target of FIS Polycomb group repressive complex2 (PRC2), establishing the molecular basis for FIS PRC2-mediated endosperm cellularization (Hehenberger et al, 2012).…”
Section: Differential Regulatory Mechanisms In Embryo and Endospermmentioning
confidence: 99%
“…S17), implicating a differential transcriptional regulation between embryo and endosperm. It was previously reported that TFs of MADS function in seed and endosperm development (Kang et al, 2008;Sreenivasulu et al, 2008;Bemer et al, 2010;Le et al, 2010;Agarwal et al, 2011;Hehenberger et al, 2012). AGL62, a MADS protein of Arabidopsis, is the direct target of FIS Polycomb group repressive complex2 (PRC2), establishing the molecular basis for FIS PRC2-mediated endosperm cellularization (Hehenberger et al, 2012).…”
Section: Differential Regulatory Mechanisms In Embryo and Endospermmentioning
confidence: 99%
“…Developmental defects are associated with increased expression of PHE1 and many other genes in the endosperm (Kang et al, 2008;Kö hler et al, 2003b;Erilova et al, 2009), suggesting that the main function of the FIS PcG complex is to suppress dosage sensitive genes in the endosperm. Support for this idea stems from experiments showing that fis mutants can form viable seeds if a sexually derived fis embryo is supported by an autonomously developing diploid endosperm (Nowack et al, 2007).…”
Section: Regulation Of Dosage Sensitive Gene Expression In the Endospermmentioning
confidence: 99%
“…The existence of three redundant pathways that 144 control endosperm cellularization has been recently pro-145 posed (Kang et al 2013). The first pathway regulates 146 endosperm cellularization through the action of APETALA 147 2 (AP2) and the MADS-box transcription factor AGL62 148 (Kang et al 2008 (Jofuku et al 1994;Okamuro et al 1997;Riechmann and 159 Meyerowitz 1998). AP2 is involved in a great variety of 160 developmental processes, including endosperm cellular-161 ization.…”
mentioning
confidence: 99%
“…The expression 171 level AGL62 correlates with endosperm cellularization in a 172 dosage-dependent way, suggesting that it represents a key 173 regulator of endosperm cellularization and consequently of 174 seed size determination. Accordingly, the agl62 mutants 175 have precocious endosperm cellularization and a small 176 seed phenotype (Kang et al 2008;Kradolfer et al 2013), 177 while increased AGL62 expression correlates with a delay …”
mentioning
confidence: 99%
See 1 more Smart Citation